Biological researches around the Belarusian Antarctic Expedition’s camp «Vechernyaya Mountain» (East Antarctica) - Giginyak, Yu.; Borodin, O. (Ukrainian Antarctic Journal, 2012)
The study was done in the region where Bilorussian Antarctic Expedition set up a field camp (’Gora Vechernyaya’). The camp is situated within oasis Molodëzhnyj on the shore of the <span style="display: inline !important; float: none; background-color: #ffffff; color: #202122; font-family: sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Cosmonauts Sea at the edge of the Eastern Antarctica (the sea lies approximately between 33º and 54º E). There were found three main groups of microalgae: Chyanophyta, Chlorophyta and Euglenophyta. Of 79 species of algae we found in the studied Antarctic lakes, 75 occur in freshwater lakes of Bielorus. Of 19 species of lichens, seven are found in Bielorus. All three species of Bryophyta are common in Bielorus. Zooplankton of the freshwater lakes is mostly represented by rotifers. Among the fish, the most frequent was Trematomus newnesi. There were counted the pinnipeds (2 species) and birds (10 species). We determined the caloric value of fishes. The organic matter content in Antarctic hydrobionts varies from 16,8 to 98%, and the caloricity from 0,5 to 8,3 cal/mg dry matter. There was seen a high level of similarity between the fauna and flora of terrestrial and freshwater ecosystems in the region where BAE worked and the temperate zone of the Northern Hemisphere (Europe, Bielorus). There was supposed taxonomic similarity of algae-bacteriae compositions of the bottom sediments from the freshwater lakes of Antarctica and the got springs of Kamchatka.